The Effect of 2,4-D on Callus Growth of Diospyros discolor Willd in Media MS in Vitro - Illahi, Ana Karunia; Ratnasari, Evie; Dewi, Sari Kusuma (LenteraBio : Berkala Ilmiah Biologi, 2022)
Bisbul (Diospyros discolor Willd) was a potential medicine plant that had several secondary metabolites such as alkaloids, flavonoids, saponins, tannins, and steroids. Bisbul was increasingly difficult to find and propagation techniques were still carried out vegetatively such as grafting which took a long time to become seedlings. This could be overcome by means of propagation through tissue culture techniques. The aim of this research was to determine the effect and optimal concentration of 2,4-D (Dichlorophenoxyacetic acid) on callus growth of bisbul leaves on MS (Murashige and Skoog) in vitro. The research was conducted experimentally using a Completely Randomized Design with one factor was the concentration of 2,4-D (0 mg/l, 2 mg/l, 4 mg/l, and 6 mg/l). The research was carried out fifth times in order to obtain 20 treatment units. The parameters measured included the percentage of explant curving, the percentage browning, and callus morphology. Data analysis was carried out descriptively quantitatively. The results showed that bisbul leaf explants at a concentration of 2,4-D 4 mg/l had an effect on growing callus. The concentration of 2,4-D 4 mg/l had a curved explant percentage of 90%, a browning 20%, and callus morphology was white and had a non friable texture.